Menjembatani Transisi dari Kesadaran ke Aksi Lingkungan: Pendekatan Partisipatif Berbasis Keterlibatan Komunitas melalui Inovasi Ecobrick dalam Pemberdayaan Masyarakat - Raicha Oktafiani; Aryani Dwi Kesumawardani; Muhammad Farhan Barata; Salsabila (WISE Pendidikan Indonesia, 2025)
This study examines the implementation of an economic ecobrick program conducted by community service students (KKN) in Sumur Batu Village, Teluk Betung Utara District, Bandar Lampung. The program aimed to reduce plastic waste while fostering community empowerment through creative and environmentally friendly activities. Using a qualitative descriptive approach, data were collected through. Interviews, observations, and documentation during a 30-day period of engagement. The findings show that community participation, particularly from local women’s groups (PKK), was highly enthusiastic. Several creative products were successfully produced, including keychains, headbands, and decorative mirrors made from household plastic waste, as well as compact ecobrick bottles that served as simple building prototypes. Environmentally, the program contributed to reducing plastic waste and raising community awareness about sustainable waste management. Economically, the products demonstrated initial potential as marketable items, although their development remained limited by the availability of raw materials and variations in product design. In conclusion, the ecobrick program not only functioned as a solution for plastic waste management but also as a means of fostering local creative economy initiatives. The program’s sustainability requires continued support from community organizations and local government